Theoretical insight into the hydroxylamine oxidoreductase mechanism - Fernández, María Laura (2008)
The multiheme enzyme hydroxylamine oxidoreductase from the autotrophic bacteria Nitrosomonas europaea catalyzes the conversion of hydroxylamine to nitrite, with a complicate arrangement of heme groups in three subunits. As a distinctive feature, the protein has a covalent linkage between a tyrosyl residue of one subunit and a meso carbon atom of the heme active site of another. We studied the influence of this bond in the catalysis from a theoretical perspective through electronic structure calculations at the density functional theory level, starting from the crystal structure of the protein. Geometry optimizations of proposed reaction intermediates were used to calculate the dissociation energy of different nitrogen containing ligands, considering the presence and absence of the meso tyrosyl residue. The results indicate that the tyrosine residue enhances the binding of hydroxylamine, and increases the stability of a Fe III NO intermediate, while behaving indifferently in the Fe II NO form. The calculations performed on model systems including neighboring aminoacids revealed the probable formation of a bidentate hydrogen bond between the Fe III H 2 O complex and Asp 257, in a high-spin aquo complex as the resting state. Characterization of non-planar heme distortions showed that the meso-substituent induces significant ruffling in the evaluated intermediates.